Influencing factors of health-related quality-of-life perceived by both children/adolescents patients with type-1 diabetes mellitus and their parents: A North-African study [version 2; peer review: 2 approved] - Jihene Bouguila; Hichem Ben Said; Lamia Boughamoura; Helmi Ben Saad; Khansa Derbel; Raoudha Kebeili; Imen Ben Abdesselem (F1000Research)
Aim To determine the influencing factors of health-related quality-of-life (HRQoL) perceived by North-African children/adolescents with type-1 diabetes-mellitus (T1DM) and their parents. Methods It was a cross sectional study conducted in Tunisia. A total of 116 patients ( ie ; 43 children and 73 adolescents) and their parents were included. The Arabic validated version of the Pediatric Generic Core Quality-of-Life Inventory 4.0-Scale (PedsQL4.0) was used to evaluate the HRQoL of children/adolescents as perceived by patients and parents. The dependent data were the patients’ self-report and the parents’ proxy-report of the PedsQL4.0 total scores, and the independent data were the patients and parents characteristics. Results Patients’ PedsQL4.0 total score was influenced significantly by siblings in the family > 2; lipodystrophy, and glycosylated hemoglobin (HbA1C). The combination of these factors explained 34.84% of the PedsQL4.0 total score variability. Parents’ PedsQL4.0 total score was influenced significantly by lipodystrophy, siblings; body mass index (BMI), hypoglycemia episodes, and HbA1C. The combination of these factors explained 56.92% of the PedsQL4.0 total score variability. Conclusion T1DM patients self-reported HRQoL was influenced by siblings in the family > 2; lipodystrophy, and HbA1C. The parents’ proxy-report HRQoL was influenced by lipodystrophy, siblings, BMI, hypoglycemia episodes, and HbA1C.